The emergence of nanoporous materials in lung cancer therapy. Issue 1 (31st December 2022) - Radhakrishnan, Deepika; Mohanan, Shan; Choi, Goeun; Choy, Jin-Ho; Tiburcius, Steffi; Trinh, Hoang Trung; Bolan, Shankar; Verrills, Nikki; Tanwar, Pradeep; Karakoti, Ajay; Vinu, Ajayan
ABSTRACT: Lung cancer is one of the most common cancers, affecting more than 2.1 million people across the globe every year. A very high occurrence and mortality rate of lung cancer have prompted active research in this area with both conventional and novel forms of therapies including the use of nanomaterials based drug delivery agents. Specifically, the unique physico-chemical and biological properties of porous nanomaterials have gained significant momentum as drug delivery agents for delivering a combination of drugs or merging diagnosis with targeted therapy for cancer treatment. This review focuses on the emergence of nano-porous materials for drug delivery in lung cancer. The review analyses the currently used nanoporous materials, including inorganic, organic and hybrid porous materials for delivering drugs for various types of therapies, including chemo, radio and phototherapy. It also analyses the selected research on stimuli-responsive nanoporous materials for drug delivery in lung cancer before summarizing the various findings and projecting the future of emerging trends. This review provides a strong foundation for the current status of the research on nanoporous materials, their limitations and the potential for improving their design to overcome the unique challenges of delivering drugs for the treatment of lung cancer. Graphical abstract: uf0001